The comparative analysis of web applications frameworks in the Node.js ecosystem - Miłosierny, Bartosz; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2021)
The subject of the research was the comparative analysis of three frameworks for building web applications, i.e. Express, Hapi and Koa, operating in the Node.js ecosystem. An experiment was prepared consisting of a number of scenarios, during which the server response times to incoming requests from the client were measured. As part of the work, server test applications handling HTTP requests (GET, POST, PUT, DELETE) performing typical data operations were implemented. The applications contained the same functionalities and were built using the three tested frameworks. In individual scenarios, 1000 requests of a given type were sent from independent clients, the times of successive responses were measured and their averages were calculated. On the basis of the obtained results, Hapi and Koa frameworks for GET, POST, PUT, DELETE requests, operating on one object or a string "Hello World!" have achieved the best, although very similar, response times. In the case of the GET request, the Koa framework proved to be the best for higher loads, achieving response times approximately 20% better than the Express framework. For high loads, the Hapi framework achieved the worst results, reaching over 2 times longer response times than the Koa framework.